Biopsychosocial correlates of body satisfaction in 7- to 8-year old children: a cross-sectional and prospective investigation - Danielle L. Smith; Stephanie R. Damiano; Siân A. McLean; Eleanor H. Wertheim; Susan J. Paxton (Journal of Eating Disorders)
Abstract Background Biopsychosocial factors have been associated with body satisfaction/dissatisfaction and related body image concerns in adolescence; however, few studies have investigated these relationships in middle childhood, an important developmental phase for body satisfaction. This study investigated relationships between a range of biological (body mass index), psychological (child anxiety/depression, self-esteem, and self-oriented and socially prescribed perfectionism) and sociocultural (mother’s body dissatisfaction and comments about child’s appearance, father’s body dissatisfaction and comments about child’s appearance, peer teasing and child’s media exposure) factors and body satisfaction cross-sectionally and longitudinally in a sample of 7- and 8-year-old children. Methods In this study, participants from the longitudinal Children’s Body Image Development Study (in which children had been followed-up annually from 3 years old) were assessed by interview at 7 years old (Time 1; n = 293: girls = 167, boys = 126) and 8 years old (Time 2; n = 222; girls = 126, boys = 96) and their parents completed a questionnaire at each time point. Results Multiple regression analyses revealed that child self-esteem, socially prescribed perfectionism, and mother body dissatisfaction in the total sample at 7-years, as well as child self-esteem and mother body dissatisfaction in the total sample at 8-years were significant unique cross-sectional correlates of child body satisfaction. While self-esteem outcomes were replicated at both time points for boys and girls, some differences in patterns were found for other variables in the subsamples of boys versus girls across time points. Prospectively in partial correlations (controlling for Time 1 child body satisfaction), mother’s body dissatisfaction predicted later child body satisfaction in boys and child self-esteem predicted later body satisfaction in girls. However, no longitudinal biopsychosocial predictors were identified as contributing unique variance in child body satisfaction from 7- to 8-years old after accounting for Time 1 (7-yearold) child body satisfaction. Conclusions These findings point to important psychosocial factors that are consistently related to body satisfaction in children and could be targets for intervention, but also suggest that a number of biopsychosocial variables develop concurrently with body satisfaction.